'Prefer not to say': diversity and diversity reporting at the bar of England & Wales. Issue 3 (2nd September 2017) - Vaughan, Steven
ABSTRACT: The Bar of England & Wales, like the wider legal profession, does not reflect the society it serves. The current data published by the Bar Standards Board (BSB) suggests a profile in relation to gender and ethnicity that gives serious cause for concern. As regards additional diversity characteristics, the BSB (and others) have accepted that the existing datasets are not wholly reliable because of poor response rates to associated diversity questionnaires. In 2011, the Legal Services Board (LSB) introduced mandatory guidance that obliged its daughter regulators to put into place rules that relate to diversity monitoring and reporting across the legal profession. This paper is concerned with how the BSB has operationalised that statutory guidance in respect of the Bar. Drawing on data gathered from the websites of 160 chambers, I show significant non-compliance with the reporting rule, and question both how the BSB itself reports on diversity data and the drafting of the reporting rule. I ask whether non-compliance is partly a function of the complexity seen in how the BSB has made operational the LSB's reporting requirements. My data also suggests that the BSB should target its enforcement and educational approaches to the reporting rule to small and medium sized chambers.